A Rare Instance of Co-existing Malignancy in Ectopic and Orthotopic Thyroid Gland - Naznin, Afroza; Salekin, Mohammad Simoon; Yasmin, Farida; Sharmin, Samira; Uddin, Md Monir; Rahman, Hosne Ara (Bangladesh Journal of Nuclear Medicine, 2025)
Ectopic thyroid tissue can be found anywhere in the midline from the base of the tongue to mediastinum. Ectopic thyroid tissue may also be involved in the same pathological processes like tumors, inflammation and hyperplasia as normal, orthotopic thyroid gland. Besides, the appearance of such tissue in rare locations may result in diagnostic and therapeutic dilemmas. We report an extremely rare case of simultaneously occurring papillary carcinoma in ectopic subglottic thyroid and orthotopic thyroid gland in a young Asian male. The patient presented with symptoms completely unrelated to thyroid disorder, and went through an eventful journey before being correctly diagnosed and properly treated. Bangladesh J. Nuclear Med. 27(2): 317-319, 2024